2013
DOI: 10.1155/2013/527182
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Mixed Convection Heat Transfer between a Sphere Particle and High Pressure Water in Pseudocritical Zone

Abstract: Mixed convection heat transfer between supercritical water and particles is a major basic problem in supercritical water fluidized bed reactor, but little work focused on this new area in the past. In this paper, a numerical model fully accounting for thermophysical property variation has been established to investigate heat transfer between supercritical water and a single spherical particle under gravity. Flow field, temperature field and Nusselt number are analyzed based on the simulation results. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The authors noticed that due to a rise in the convection parameter, the momentum boundary layer thickness was raised. Some other studies in the literature on the mixed convection, forced convection and free convection are given by Labib et al (2013), Wei et al (2013), Gorla et al (2017), Rostami et al (2018) and Jamaludin et al (2019).…”
mentioning
confidence: 99%
“…The authors noticed that due to a rise in the convection parameter, the momentum boundary layer thickness was raised. Some other studies in the literature on the mixed convection, forced convection and free convection are given by Labib et al (2013), Wei et al (2013), Gorla et al (2017), Rostami et al (2018) and Jamaludin et al (2019).…”
mentioning
confidence: 99%
“…The flow is stable and symmetric within the range of Re less than 210 . Previous studies have shown that the flow of SCW around particles at Re ≤ 200 is a stable symmetrical flow. The Re range of this work is 25–200. The physical properties of SCW vary with temperature, which causes the drag force of interactive particles to change.…”
Section: Methodsmentioning
confidence: 77%
“…Thus, when considering physical properties, Re and distance must be considered simultaneously. In the research of SCW, the effect of physical properties can be expressed as a function of physical properties. The effect of physical properties is obtained by analysis as eq . Therefore, the drag ratio correlation in SCW is expressed as eq .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations